Risk-Stratified and Response-Adapted Therapy for Pediatric Hodgkin Lymphoma in Argentina: The GATLA Experience - David Veron; Patricia Streitenberger; Mónica Matus; Pedro Negri Aranguren; Alejandra Costa; Daniela Morell; Sergio Terrasa; E. Mauricio Castellanos; Pedro de Alarcon; Eduardo Dibar; Mónica Makiya (Advances in Hematology)
Conclusion: The international cooperation made it possible to significantly improve the outcomes of patients with advance disease in Argentina compared with our previous experience (7-PHD-96: COPP–ABV × 6 + IFRT Bulky Disease or PR (20/25 Gy): 5yOS: 85%, 5yEFS: 67%), reduce the number of patients who required radiotherapy, and reproduce the European experience for HR patients in a totally different context.